Specific Microbial Communities Associate with the Rhizosphere of Welwitschia mirabilis, a Living Fossil. - Angel Valverde (PLoS ONE, 2016)
Welwitschia mirabilis is an ancient and rare plant distributed along the western coast of Namibia and Angola. Several aspects of Welwitschia biology and ecology have been investigated, but very little is known about the microbial communities associated with this plant. This study reports on the bacterial and fungal communities inhabiting the rhizosphere of W. mirabilis and the surrounding bulk soil. Rhizosphere communities were dominated by sequences of Alphaproteobacteria and Euromycetes, while Actinobacteria, Alphaproteobacteria, and fungi of the class Dothideomycetes jointly dominated bulk soil communities. Although microbial communities within the rhizosphere and soil samples were highly variable, very few "species" (OTUs defined at a 97% identity cut-off) were shared between these two environments. There was a small 'core' rhizosphere bacterial community (formed by Nitratireductor, Steroidobacter, Pseudonocardia and three Phylobacteriaceae) that together with Rhizophagus, an arbuscular mycorrhizal fungus, and other putative plant growth-promoting microbes may interact synergistically to promote Welwitschia growth.